Reducing interruptions to continuous enteral nutrition in the intensive care unit: A comparative study - Williams, T.; Leslie, Gavin; Leen, T.; Mills, L.; Dobb, G. (Wiley-Blackwell Publishing Ltd., 2013)
Aims and objectives: To develop and test strategies to reduce interruptions to enteral feeding to improve practice and promote attainment of nutritional goals. Background: Enteral nutrition is preferred for feeding patients in the intensive care unit who are unable to have oral nutrition. Interruption to feeding is likely to be a major contributor to patients not receiving their prescribed nutrition goals. Design: Prospective before (May–November 2009) and after (March–September 2010) study. Method: Patients admitted to the intensive care unit (except cardiac surgery) and who were eligible to receive enteral nutrition were enrolled. After gaining Ethics Committee approval, baseline data were collected to identify interruptions to enteral nutrition. Nurse-led multidisciplinary teams developed interventions to target specific reasons for interruption. Change champions implemented the improvements after staff were provided with an education package. Post intervention data were then collected.Results: Six hundred and fifty-three patients received enteral nutrition with the majority (88%) fed within 48 hours. Considering the first 28 days of feeding for patients fed longer than 24 hours (505 patients), the number of interruptions for patients who had an interruption decreased from 907–662. Interruptions due to gastrointestinal issues decreased (14 vs 10%), while those due to airway issues, enteral nutrition delivery system problems and other interruptions were similar before-and-after the practice change. Time lost to feeding because of interruptions was similar between groups. Conclusion: Targeted strategies to enteral feeding practice resulted in a reduction to the number of interruptions but not the duration of enteral nutrition lost to interruption. Reducing unnecessary interruption of feeding circuits is likely to minimise the risk for splash injury and contamination of feeding sets through less manipulation and interruption to enteral nutrition flow. Relevance to clinical practice: Review of practice may reveal opportunities for improvement. Nurse champions can facilitate change processes to improve care.